1976
DOI: 10.1002/jcp.1040880109
|View full text |Cite
|
Sign up to set email alerts
|

SV40 transformation of mouse brain cells: Critical role of gene A in maintenance of the transformed phenotype

Abstract: Brain cells derived from the NIH Swiss mouse strain have been established in tissue culture. Astrocytic neuroglial cells, identified by morphology and staining properties, predominate. The brain cell culture was successfully transformed with SV40 wild type virus and with a representative early (A239) and late (C219) mutant. When subjected to growth analysis the A239 transformant displayed selective loss of six characteristics of the transformed phenotype at the restrictive temperature (40.5 degrees C): doublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Single cell suspensions were fixed in 70% ethanol/30% 50 mM MgCl2, and stained with mithramycin, which binds stoichiometrically to DNA (16 Thus, the characteristics used to define the transformed phenotype (cell morphology, colony formation on plastic or on soft agar, and saturation density) were quite temperature sensitive in the tsA transformed cells. The WT transformants were also somewhat temperature sensitive, as has occasionally been observed in other WT SV40-transformed cell populations (2,3,5,18). The molecular mechanism of the thermal sensitivity of transformed cells is a well described, but as yet poorly understood, phenomenon (19,20).…”
mentioning
confidence: 69%
“…Single cell suspensions were fixed in 70% ethanol/30% 50 mM MgCl2, and stained with mithramycin, which binds stoichiometrically to DNA (16 Thus, the characteristics used to define the transformed phenotype (cell morphology, colony formation on plastic or on soft agar, and saturation density) were quite temperature sensitive in the tsA transformed cells. The WT transformants were also somewhat temperature sensitive, as has occasionally been observed in other WT SV40-transformed cell populations (2,3,5,18). The molecular mechanism of the thermal sensitivity of transformed cells is a well described, but as yet poorly understood, phenomenon (19,20).…”
mentioning
confidence: 69%
“…TA binds to DNA (7), and, after incuba-pacity of the early region of the SV40 genome tion at 440C, TA obtained from tsA-transformed (25,31). Second, all known tsA mutants synthe-As control, we demonstrate that a typical tsA MgCl2, 0.15 mM CaCl2, 0.1% [grams/100 milliliters] mutant-transformed cell line that continues to Difco gelatin, 0.05 M sodium barbital, pH 7.5) to express TA at the restrictive temperature (as give about 20% (vol/vol) suspensions, sonicated at 0 do most tsA-transformed cell lines [3,6,14,24, to 40C for 2 min, and stored at -70°C; these TA- 29,30]) also continues to express TSTA. In a containing lysates were used directly as TA or after separate communication we demonstrate that clarification by centrifugation at either 1,000 x g for several different cell lines transformed by tsA 10 min or 17,000 x g for 15 min.…”
mentioning
confidence: 75%
“…Genetic studies with simian virus 40 (SV40) now show in addition that the TA from tsAmutants indicate that the "early" gene A is transformed cells is more thermolabile by comessential for the initiation ofviral replication in plement fixation (CF). permissive infection and for the initiation and Tumor-specific transplantation antigen maintenance of transformation in nonpermis-(TSTA) is more difficult to assay and has been sive infection (3,6,9,14,22,23,25,26,29,30). less thoroughly investigated than TA, although The SV40-specific antigens T, TST, and U are its expression also requires part of the early expressions of this early region of the SV40 region ofthe SV40 genome (17,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson and Lehman (1978) reported that a n apparent growth arrest, assayed as number of cells, in tsA mutant-transformed Chinese hamster embryo fibroblasts at nonpermissive temperature is attributable to a balance of cell death and multiplication but not to arrest in the particular phases of the cell cycle. Arrest of growth in tsA mutant-transformed fibroblasts (Martin and Stein, 1976;Brockman, 1978;Butel and Soule, 1978;Hiscott and Defendi, 1979;O'Neill et al, 1980) and in tsA mutant-transformed cells that retain differentiated functions (Anderson and Martin, 1976;Chou, 1978a;Maltzman et al, 1979;Schlegel-Haueter et al, 1980) has been reported.…”
Section: Discussionmentioning
confidence: 98%